Knowledge use analysis as a way to understand planning conflicts. Two cases from Gothenburg, Sweden. (May 2022) - Stepanova, Olga; Saldert, Hannah
Abstract: Knowledge integration is often highlighted as a necessary precondition for sustainable urban planning. It is also a way to manage conflicts in complex institutional settings and practices. However, analyses of knowledge use practices in empirical planning cases are rare. In this paper, we aim to better understand knowledge-related aspects of conflict development and resolution. We perform a detailed analysis of how different types of knowledge are used by conflicting actors in two urban development projects in Gothenburg, Sweden and reflect on the implications that such practices have for conflict resolution. We show how integration of knowledge can be identified in the context of planning conflicts and how knowledge use related roots of conflicts become more visible. Attention to how knowledge is used and integrated in conflict management can shed more light on shortcomings of resolution processes and serve as a base to improve conflict resolution towards more lasting, long-term oriented, and therefore more sustainable solutions. Highlights: Theory of knowledge use is applied on two empirical cases of planning conflicts. A detailed analysis of knowledge use and its implications for conflict resolution. Through the analysis knowledge use related roots of conflicts are made visible. Knowledge analysis sheds more light on shortcomings of resolution processes. Knowledge analysis may serve as a base to improve conflict resolution in planning.